2007
DOI: 10.1155/2007/90752
|View full text |Cite
|
Sign up to set email alerts
|

Silver Modified Degussa P25 for the Photocatalytic Removal of Nitric Oxide

Abstract: A study of the photocatalytic behaviour of silver modified titanium dioxide materials for the decomposition and reduction of nitric oxide (NO) gas has been carried out. The effects of silver loading, calcination temperature, and reaction conditions have been investigated. Prepared photocatalysts were characterised using XRD, TEM, and XPS. A continuous flow reactor was used to determine the photocatalytic activity and selectivity of NO decomposition in the absence of oxygen as well as NO reduction using CO as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 21 publications
3
29
0
1
Order By: Relevance
“…Before the photocatalytic reactions were studied, the photocatalyst was stirred in the MB solution in the dark overnight to reach adsorption-desorption equilibrium. [30] From the XPS results presented here, the gold oxidation state is zero (elemental), which is expected to boost the PC activity. The PC activity can be classified as either significantly boosted, as in the case of Pd and Au, or slightly enhanced (or even negatively influenced), as in the case of Ag and Pt.…”
Section: Photocatalytic Activity Of Porous M/tiomentioning
confidence: 82%
“…Before the photocatalytic reactions were studied, the photocatalyst was stirred in the MB solution in the dark overnight to reach adsorption-desorption equilibrium. [30] From the XPS results presented here, the gold oxidation state is zero (elemental), which is expected to boost the PC activity. The PC activity can be classified as either significantly boosted, as in the case of Pd and Au, or slightly enhanced (or even negatively influenced), as in the case of Ag and Pt.…”
Section: Photocatalytic Activity Of Porous M/tiomentioning
confidence: 82%
“…However, in the presence of C4H10, it could further promote the formation of N2 from NO2 [11,12,32], resulting in the decrease of NO2 selectivity along with the increase of NOx removal. On the other hand, in the absence of C4H10, NO2 might be oxidized to nitrates or nitrites [20,22].…”
Section: Characterization Of Photocatalystsmentioning
confidence: 99%
“…For a traditional approach, the powder particles photocatalyst has been considered in most of the photocatalytic NOx removal [20][21][22][23]. Despite wide-spread use, this approach suffers from many drawbacks including how to recycle/regenerate the photocatalysts, and poorly exposed to the light source.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have attempted to improve the photocatalytic performance of Degussa P25 further by doping, sensitization and preparing its composites [7][8][9] photocatalytic performance [7]. Neil Bowering et al reported the photocatalytic activity of silver modified Degussa P25 materials for the decomposition and reduction of nitric oxide [8].…”
Section: Introductionmentioning
confidence: 99%
“…Neil Bowering et al reported the photocatalytic activity of silver modified Degussa P25 materials for the decomposition and reduction of nitric oxide [8]. Hao Zhang et al reported the P25-graphene composite photocatalyst possessed great absorptivity of dyes with extended light absorption range, and efficient charge separation properties simultaneously [9].…”
Section: Introductionmentioning
confidence: 99%